2015
DOI: 10.1038/ni.3279
|View full text |Cite
|
Sign up to set email alerts
|

PARP9-DTX3L ubiquitin ligase targets host histone H2BJ and viral 3C protease to enhance interferon signaling and control viral infection

Abstract: Enhancing the response to interferon could offer an immunological advantage to the host. In support of this concept, we used a modified form of the transcription factor STAT1 to achieve interferon hyperresponsiveness without toxicity and markedly improve antiviral function in transgenic mice and transduced human cells. We found that the improvement depends on expression of a PARP9-DTX3L complex with distinct domains for interaction with STAT1 and for activity as an E3 ubiquitin ligase that acts on host histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
195
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(217 citation statements)
references
References 60 publications
6
195
1
1
Order By: Relevance
“…Interferon stimulation of cells leads to activation of its downstream transcription factor, STAT1, and subsequent binding of STAT1 to genomic loci to induce proinflammatory gene expression. Zhang et al (2015) showed that the phenotypic outcomes of a STAT1 mutant that is hyperresponsive to interferon signaling depend on the PARP-9-DTX3L complex. Multiple domains of PARP-9 and DTX3L are required for the interaction with STAT1.…”
Section: Role Of Parp Monoenzymes and Catalytically Inactive Parps Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferon stimulation of cells leads to activation of its downstream transcription factor, STAT1, and subsequent binding of STAT1 to genomic loci to induce proinflammatory gene expression. Zhang et al (2015) showed that the phenotypic outcomes of a STAT1 mutant that is hyperresponsive to interferon signaling depend on the PARP-9-DTX3L complex. Multiple domains of PARP-9 and DTX3L are required for the interaction with STAT1.…”
Section: Role Of Parp Monoenzymes and Catalytically Inactive Parps Inmentioning
confidence: 99%
“…5E; Zhang et al 2015). Interferon stimulation of cells leads to activation of its downstream transcription factor, STAT1, and subsequent binding of STAT1 to genomic loci to induce proinflammatory gene expression.…”
Section: Role Of Parp Monoenzymes and Catalytically Inactive Parps Inmentioning
confidence: 99%
“…The 3C proteases produced by EMCV and certain other picornaviruses have been shown to be targeted for polyubiquitylation and 26S proteasome-catalyzed degradation [6–9], although the function of this degradation has not been fully explicated. 3C proteases are critical for successful virus replication, and limiting their concentrations may serve to help maximize replication efficiency through minimizing 3C pro cytotoxicity [10] or may represent an antiviral defense mechanism [11]. …”
Section: Introductionmentioning
confidence: 99%
“…The kinetic parameters that characterize UBR1-catalyzed polyubiquitylation, however, suggest that this pathway may not be a major contributor to marking the 3C pro for destruction in vivo [13]. The E3 that functions in the UbcH5-containing pathway is probably DTX3L, a RING-type E3 recently reported to catalyze EMCV 3C pro polyubiquitylation and contribute to 3C pro degradation in virus-infected cells [11]. DTX3L complexed with PARP9 also functions as a component of a potent antiviral response system that promotes interferon-stimulated gene expression [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation